"A Bridge Thrown Over the Stream of Time": "The Triumph of Life" between the Divina Commedia and "Shelley Disfigured". Issue 2 (October 2016) - Guthrie, Bernadette
Abstract : This essay argues that both the material history of the manuscript of Percy Bysshe Shelley's "The Triumph of Life" and its own presentation of literary history challenge longstanding readings of the poem as an illustration of the fundamentally modern nature of Shelley's romanticism. It demonstrates how Shelley's final poem represents instead an "untimely" combination of pre-modern and modern understandings of (literary) history and associates these understandings with two texts central to the poem's own literary history: Dante's Divina Commedia, whose influence on Shelley's poem is felt both thematically and metrically, and Paul de Man's "Shelley Disfigured, " one of the most influential twentieth-century readings of "Triumph." It demonstrates the poem's liminal position between these texts by drawing on formal, historical, and archival approaches to Shelley's poem.